Polarization sensitive optical coherence tomography with single input for imaging depth-resolved collagen organizations - Peijun Tang; Mitchell A. Kirby; Nhan Le; Yuandong Li; Nicole Zeinstra; G. Nina Lu; Charles E. Murry; Ying Zheng; Ruikang K. Wang (Light: Science & Applications, 2021)
Discrete differential geometry-based polarization tracing method enables PSOCT imaging of depth-resolved collagen organizations.